Plasma p‐tau181, p‐tau217, and other blood‐based Alzheimer's disease biomarkers in a multi‐ethnic, community study - Brickman, Adam M.; Manly, Jennifer J.; Honig, Lawrence S.; Sanchez, Danurys; Reyes‐Dumeyer, Dolly; Lantigua, Rafael A.; Lao, Patrick J.; Stern, Yaakov; Vonsattel, Jean Paul; Teich, Andrew F.; Airey, David C.; Proctor, Nicholas Kyle; et al. (Alzheimer's & dementia, 2021)
Introduction Blood‐based Alzheimer's disease (AD) biomarkers provide opportunities for community studies and across ethnic groups. We investigated blood biomarker concentrations in the Washington Heights‐Inwood Columbia Aging Project (WHICAP), a multi‐ethnic community study of aging and dementia. Methods We measured plasma amyloid beta (Aβ)40, Aβ42, total tau (t‐tau), phosphorylated tau (p‐tau)181, and p‐tau217, and neurofilament light chain (NfL) in 113 autopsied participants (29% with high AD neuropathological changes) and in 300 clinically evaluated individuals (42% with clinical AD). Receiver operating characteristics were used to evaluate each biomarker. We also investigated biomarkers as predictors of incident clinical AD. Results P‐tau181, p‐tau217, and NfL concentrations were elevated in pathologically and clinically diagnosed AD. Decreased Aβ42/Aβ40 ratio and increased p‐tau217 and p‐tau181 were associated with subsequent AD diagnosis. Discussion Blood‐based AD biomarker concentrations are associated with pathological and clinical diagnoses and can predict future development of clinical AD, providing evidence that they can be incorporated into multi‐ethnic, community‐based studies.